Profit maximization in ADN through voltage control and DR management with networked community micro-grids - Singh, Shailendra (2023)
Large-scale installations of utility and customer's owned distributed technologies at low and medium voltage networks have drawn the distribution system operator's attention towards enhancing energy efficiency and economics of distribution grids. It can be achieved by deploying suitable energy-saving programs and unlocking the benefits of networked community microgrids (N-CMGs). In this context, the paper introduces an integrated methodology by enabling the volt/VAR optimization and demand response management scheme in the presence of N-CMGs that leverage distributed energy resources, flexible loads, and a smart energy management system. The stochastic objective function has been formulated regarding net profit value maximization in the presence of N-CMG assets. Further, efficient cascaded droop (Volt/VAR, Volt/Watt) control algorithms have been developed for real-time control of N-CMGs operations under unexpected transient conditions. The simulated outcomes authenticate that the proposed integrated method maximized the net profit values in terms of reduced purchased electricity cost and improved energy efficiency. Moreover, the developed real-time cascaded droop controller for N-CMGs successfully handles the unprecedented event's impact on system security during real-time operation.